Three-Dimensional Unmanned Aerial Vehicle Path Planning in Simulated Rugged Mountainous Terrain Using Improved Enhanced Snake Optimizer (IESO) - Wuke Li; Kongwen Zhang; Qi Xiong; Xiaoxiao Chen (World Electric Vehicle Journal, 2025)
The challenging terrain and deep ravines that characterize mountainous regions often result in slower path planning and suboptimal flight paths for unmanned aerial vehicles (UAVs) when traditional meta-heuristic optimization algorithms are employed. This study proposes a novel Improved Enhanced Snake Optimizer (IESO) for three-dimensional path planning and tested it in a simulated rugged mountainous terrain with obstacles and a restricted “no-fly zone”. The initialization process in the enhanced snake optimizer is refined by integrating the Chebyshev chaotic map. Additionally, a non-monotonic factor is introduced to modulate the “temperature”. This temperature controls the freedom of movement within the solution space. Furthermore, a boundary condition is incorporated into the dynamic opposition learning mechanism. These modifications collectively reduce the likelihood of population convergence to local optima during optimization. The feasibility of IESO is validated through time complexity and global convergence analyses. Comparative simulation experiments benchmarked IESO against five state-of-the-art biologically inspired optimization algorithms across test functions and path-planning simulated scenarios. Experimental results show that compared with five commonly used algorithms, the IESO algorithm improves the quality of flight trajectory planning by nearly 30% on average. Particularly when compared to the original SO algorithm, IESO demonstrates performance enhancement exceeding 36%, proving its superiority in UAV path planning over complex terrain.